From Collective Form to Collective Housing. Case study of Skopje Housing Pockets - Minas Bakalchev, Sasha Tasic (Roma Tre University, Department of Architecture, 2014)
Between the traditional pattern of living and new postmodern society of individualization there are persistent housing pockets of transitional forms. Neither are they historic traditional models of living nor alien forms of contemporary lifestyles. They are pockets of once intense, socially connected communities from the city that vanishes. Exactly this transitional position gives possibility of upgrading an alternative form of collective housing. On the example of the city of Skopje, where the process of modernization produces different left-over’s, pockets of housing, once traditional form of living - today as hybrid informal assemblages, opportunity is created to develop different scenarios of re-working the collective form of the city. By connecting the idea of collective form from the 1960s, as linking the “objects that have a reason to get together”, with the idea of collective living with shared ways of living together, we will produce different tactics of transformation of the urban texture. Introduction of collective form as mega-form was strategy of post earthquake reconstruction of the city of Skopje (after the 1963). Our current reconsideration of the idea of collective form is connected with the tactic of transformation of urban fragments as persistent housing pockets. Both approaches use the same theoretical references but within different design paradigm, top down on the level of the city (1960s) and bottom up on the level of local housing contexts (2010s). Through selected projects we will examine different tactics of transformation of urban fragments (upgrading, sequential linking, incision, acupuncture) as active coexistence between the existing and proposed housing typologies and between private and common realm.
Keywords: Collective form, Collective houses, Housing pocket, Urban fragments